Medical Innovation: Science, technology and practice (Taylor & Francis, 2016)
This book brings together a collection of empirical case studies featuring a wide spectrum of medical innovation. While there is no unique pathway to successful medical innovation, recurring and distinctive features can be observed across different areas of clinical practice. This book examines why medical practice develops so unevenly across and within areas of disease, and how this relates to the underlying conditions of innovation across areas of practice. The contributions contained in this volume adopt a dynamic perspective on medical innovation based on the notion that scientific understanding, technology and clinical practice co-evolve along the co-ordinated search for solutions to medical problems. The chapters follow an historical approach to emphasise that the advancement of medical know-how is a contested, nuanced process, and that it involves a variety of knowledge bases whose evolutionary paths are rooted in the contexts in which they emerge. This book will be of interest to researchers and practitioners concerned with medical innovation, management studies and the economics of innovation. Chapter 5 of this book is freely available as a downloadable Open Access PDF at www.tandfebooks.com/openaccess. It has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 3.0 license.
English
Keywords: Business innovation; Industry and industrial studies; Medical equipment and techniques; Microeconomics; clinical practice; empirical case studies; medical innovation